Pengujian Umur Simpan Kopi Arabika Bubuk Pada Jenis Kemasan dan Suhu Simpan Yang Berbeda - Elsera Br Tarigan; Edi Wardiana; Handi Supriadi (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Coffee is a beverage that is widely consumed around the world. Proper packaging and storage temperature may extend shelf life of ground coffee. The study aimed to analyze the shelf life of ground Arabica coffee stored in different packaging types and temperature, conducted at smallholder coffee plantations in Garut Regency and the Integrated Laboratory of Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, from June to August 2018. A completely randomized design in factorial was used with 3 factors and 2 replications. The first factor was the packaging type which consisted of 3 types: thick alumunium foil 65m (AF65), thick alumunium foil 130m (AF130), and thick lamination 114m (L144). The second factor was the storage temperature which consisted of 3 levels: 25 oC, 35 oC, and 45 oC, while the third factor was the storage period which consisted of 5 levels: coffee unstored, and coffee stored for 2 weeks, 4 weeks, 6 weeks, and 8 weeks. The variables observed were the water and fat content, and the analysis of shelf life was carried out using the ASLT (Accelerated Shelf Life Test) method. The results showed that during storage, the water content increased, whereas the fat content decreased. Fat content is a critical variable in determining the shelf life of coffee. The coffee in AF130 packaging has longer shelf life than in AF65 and L144. To extend the shelf life of coffee packaged in AF130 and L144 is best kept at 45 oC whereas coffee in AF65 packaging is ideally at 25 oC.